1996
DOI: 10.1016/s0893-133x(96)00097-8
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Overflow in the Nucleus Accumbens during Extinction and Reinstatement of Cocaine Self-Administration Behavior

Abstract: Both cocaine and cocaine-associated stimuli can reinstate extinguished self-administration behavior in animals. It has been suggested that reinstatement of drug-seeking behavior may be mediated by enhanced dopamine (DA) neurotransmission. To examine this hypothesis, DA overflow was measured in the nucleus accumbens (NAc) of rats during both extinction and cocaine-induced reinstatement of self-administration behavior. Rats were either allowed to self-administer cocaine for 3 hours daily for 14 days, or they rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 49 publications
9
92
3
Order By: Relevance
“…Several procedural variables may explain this apparent discrepancy. First, in all previous studies except one (Deroche et al, 1999), daily access time to cocaine was longer than the minimum of the present study (ie 1 h) and ranged between 2 and 6 h (eg de Wit and Stewart, 1981;Erb et al, 1996;De Vries et al, 1998;Lynch and Carroll, 2000;Lu et al, 2004;Fuchs et al, 2004;Schenk and Partridge 1999;Neisewander et al, 1996;Xi et al, 2004;Sutton et al, 2003;Dias et al, 2004). Thus, together with the present findings, this difference may point to the existence of some threshold duration below which most individuals readily learn to take cocaine without becoming responsive to its motivational effects and above which they begin to respond to these effects.…”
Section: Discussioncontrasting
confidence: 40%
“…Several procedural variables may explain this apparent discrepancy. First, in all previous studies except one (Deroche et al, 1999), daily access time to cocaine was longer than the minimum of the present study (ie 1 h) and ranged between 2 and 6 h (eg de Wit and Stewart, 1981;Erb et al, 1996;De Vries et al, 1998;Lynch and Carroll, 2000;Lu et al, 2004;Fuchs et al, 2004;Schenk and Partridge 1999;Neisewander et al, 1996;Xi et al, 2004;Sutton et al, 2003;Dias et al, 2004). Thus, together with the present findings, this difference may point to the existence of some threshold duration below which most individuals readily learn to take cocaine without becoming responsive to its motivational effects and above which they begin to respond to these effects.…”
Section: Discussioncontrasting
confidence: 40%
“…of cocaine. It has been reported that in rats undergoing reinstatement testing or extinction from cocaine self-administration, there is significant attenuation of cocaine-induced increases in extracellular DA in the nucleus accumbens (Neisewander et al, 1996;Mateo et al, 2005; but see Hooks et al, 1994). In contrast, electrical BSR per se appears to enhance nucleus accumbens DA (You et al, 2001).…”
Section: Ngb 2904's Inhibition Of Cocaine-triggered Reinstatement Of mentioning
confidence: 99%
“…Thus, as with the behavioral profiles produced by these early environmental insults, a presensitization of mesolimbic dopamine transmission may be a common neurochemical alteration produced by prenatal and early postnatal stress that endures into adulthood. Given the important role for NAC dopamine transmission in drug-seeking behavior (Anderson et al, 2003Bachtell et al, 2005;Di Ciano et al, 2001;Neisewander et al, 1996;Ranaldi et al, 1999;, enhanced NAC dopamine responsiveness may contribute to the enhanced cocaineseeking observed in PNS rats.…”
Section: Influence Of Pns On Neurochemical Responses To Cocainementioning
confidence: 99%